Challenges and opportunities of using DHIS2 to strengthen health information systems in the Eastern Mediterranean Region: A regional approach. Issue 1 (21st June 2019) - Sahay, Sundeep; Rashidian, Arash; Doctor, Henry V.
Abstract: Globally, there is acceptance of the role of strengthened health information system (HIS) to inform evidence‐based decision‐making and improve health services delivery. Within the context of increasing demands to generate data of high quality for monitoring progress towards SDGs, we review challenges and approaches in adopting a regional‐based approach to strengthen HIS within the WHO Eastern Mediterranean Region and its 22 member states. The HIS situation in the WHO Eastern Mediterranean Region is mixed: While some countries have developed robust HIS, others lag behind on both technological and institutional dimensions. Technically, most countries have not capitalized on the benefits of ICT advancements such as the internet, cloud, and mobile computing. As a result, systems remain manual or standalone; and data are not shareable. Institutionally, systems are broadly fragmented, with non‐standardized data, weak human resources capacity, and limited evidence of data being used to inform action. In order to consolidate efforts to enhance HISs, we recommend leveraging upon innovative information and communication technology (ICT) solutions for data capturing, processing, analysis, and reporting at either the individual or aggregate levels. Countries need to develop similar such processes in their contexts, while ensuring that they learn and build upon from their neighbors—building network of networks.